Estimating Power Needed to Fuel Electric Paratransits in Bandung - Naili Huda; Kim Peter Hassall; Aam Muharam; Kristian Ismail (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2015)
This is the preliminary finding of a study elaborating the total energy consumption when paratransits in Bandung are altered into electric and the scenario to fulfill it. Therefore, there are lots to be done further concerning result of this initial research, of which will be discussed in another publication. In this paper calculation was done to find out the volume of power needed to fuel electric paratransits in Bandung. Steps carried out include computing total energy consumption for all paratransits, clustering stations from classified routes established by local Department of Transport, and estimating the electricity demand in every clustered station. Data used for this study was acquired from Badan Pusat Statistik Kota Bandung and PT PLN DJA APD Jawa Barat and Banten. A total demand of 61.12 MWh per month will surface to charge the total of 5,521 paratransits from 38 available routes in 15 clustered stations under the assumptions that all paratransits only make 6 return travels per day, operate 30 days per month, and use batteries with 50% State of Charge.